2013
DOI: 10.1007/s00508-013-0388-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hepcidin and ferritin in haemodialysed patients

Abstract: It seems that the influence of inflammation on hepcidin levels in haemodialysed patients is not crucial and other factors (e.g. hepcidin retention) are involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…However, we previously demonstrated that the serum hepcidin level can be exclusively associated with the ferritin level in patients on MHD in the absence of apparent inflammation and independent of the levels of inflammatory cytokines [27] . Several reports have confirmed these observations [28][29][30] . These data suggest that excessive iron storage or administration increases hepcidin levels and accelerates iron sequestration in most of the cells in the body ( fig.…”
Section: Host Factorssupporting
confidence: 70%
“…However, we previously demonstrated that the serum hepcidin level can be exclusively associated with the ferritin level in patients on MHD in the absence of apparent inflammation and independent of the levels of inflammatory cytokines [27] . Several reports have confirmed these observations [28][29][30] . These data suggest that excessive iron storage or administration increases hepcidin levels and accelerates iron sequestration in most of the cells in the body ( fig.…”
Section: Host Factorssupporting
confidence: 70%
“…There was a poor correlation between hepcidin, ferritin and CRP in hemodialyzed patients. It can be concluded that the influence of inflammation on hepcidin levels in hemodialyzed patients is not important and other factors including its retention and high iron stores in end-stage renal disease also participate [23].…”
Section: Fig 2 Diagram Proposed For Assessing the Risk Of Anemia Inmentioning
confidence: 99%